Adult learners' perceptions of self-directed learning and digital technology usage in continuing professional education: An update for the digital age. Issue 1 (May 2019) - Curran, Vernon; Gustafson, Diana L; Simmons, Karla; Lannon, Heather; Wang, Chenfang; Garmsiri, Mahyar; Fleet, Lisa; Wetsch, Lyle
Mandatory continuing professional education is accepted across many professions as a re-credentialing mechanism to maintain professional competency. Self-directed learning is a widely recognized type of learning to meet mandatory continuing professional education requirements. The nature and characteristics of self-directed learning has been transformed with the growth in digital and mobile technologies, however there is minimal understanding of the role of these technologies in the self-directed learning habits of adult learners. This study sought to explore the perspectives of adult learners around the effect of digital and mobile technologies on continuing professional education activities. Semi-structured interviews were conducted with 55 adult learners from four professional groups (9 physicians; 20 nurses; 4 pharmacists; 22 social workers). Key thematic categories included perceptions of self-directed learning, self-directed learning resources, key triggers, and barriers to undertaking self-directed learning. Digital and mobile technologies emerged as important resources supporting the self-directed learning of health and human services professionals. Increasing usage and dependency on these technologies has important implications for organizational and workplace policies that can support effective self-directed learning processes in a digital age. A conceptual model is introduced to characterize the key factors defining the self-directed learning patterns and practices of adult learners in a digital age.